Upregulation of microRNA-125b-5p alleviates acute liver failure by regulating the Keap1/Nrf2/HO-1 pathway - Tao, Ya-Chao; Wang, Yong-Hong; Wang, Meng-Lan; Jiang, Wei; Wu, Dong-Bo; Chen, En-Qiang; Tang, Hong (Frontiers in Immunology, 2022)
Background: Liver failure is a life-threatening clinical problem with a high short-time mortality. Although liver transplantation is an effective therapeutic option, its application is limited due to the shortage of donor organ. MicroRNAs (miRNAs) are a group of small endogenous noncoding interfering RNA molecules involved in the biological processes and in the development of various diseases. Regulation of miRNAs and their target genes may serve as promising interventions for the treatment of liver failure. Aims: To explore the role of miR-125b-5p in the development of liver failure. Methods: Collected human liver tissue samples were categorized into 2 groups of mild-moderate liver injury and liver failure. The differentially expressed-miRNAs (DE-miRNAs) were screened and identified with the progression of liver injury through high-throughput sequencing. Among these DE-miRNAs, miR-125b-5p was selected to further investigate its role in lipopolysaccharide (LPS)/D-galactosamine (D-GalN) -induced acute liver failure (ALF) in vivo and in LPS/D-GalN-challenged huh7 cells in vitro. Results: Total of 75 DE-miRNAs were obtained, including 28 upregulated and 47 downregulated miRNAs in liver failure group as compared to the mild-moderate liver injury group. Among these DE-miRNAs, miR-125b-5p was selected for further study. It revealed that miR-125b-5p not only reduced huh7 cell apoptosis in vitro, but also relieved ALF in vivo with evidence of improved liver histology, decreased alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels, and reduced tumor necrosis factor -α (TNF-α) and IL-1β levels. Based on the result of a biological prediction website, microRNA.org, Kelch-like ECH-associated protein 1 (Keap1) was predicted as one of the potential target genes of miR-125b-5p, which was verified by the dual-luciferase reporter gene assay. Subsequent experiments in vivo and in vitro both revealed that miR-125b-5p could decrease the expression of Keap1 and cleaved caspase-3, while upregulate the expression of nuclear factor (erythroid-derived 2)-like 2 (Nrf2) and heme oxygenase-1(HO-1). Conclusion: Upregulation of miR-125b-5p can alleviate acute liver failure through regulating Keap1/Nrf2/HO-1 pathway, and regulation of miR-125b-5p may serve as an alternative therapeutic intervention for liver failure.